How Does Voxel Size of Cone-beam Computed Tomography Effect Accurate Detection of Root Strip Perforations - Afkhami, Farzaneh; Ghoncheh, Zahra; Khadiv , Fatemeh; Kaviani , Hanieh; Shamshiri , Ahmad Reza (Iranian Endodontic Journal, 2021)
Introduction: Our study aimed to assess the diagnostic accuracy of different voxel sizes for cone-beam computed tomography (CBCT) when detecting strip perforations of variable sizes. We used 0.2 and 0.3 mm3 voxel for detecting root strip perforations. Methods and Materials: This was an in vitro study conducted on 155 extracted humans’ mandibular first molars. The teeth were randomly divided into five groups (n=31). Perforation were not induced in the control group. In the remaining four groups, strip perforations of 0.5, 1, 1.5, and 2 mm diameters were created in the mesiolingual canal using #3 Gates Glidden drills. The CBCT scans were taken first with a 12×9 cm field of view (FOV), 90 kVp, 4 mA, and 0.2 mm3 voxel size for 24 sec and then with a 12×9 cm FOV, 90 kVp, 2 mA, and 0.3 mm3 voxel size for another 24 sec. Two observers evaluated the images and reported the largest diameter of perforations. The results were compared with the gold standard values (determined by an electronic digital caliper) using statistical methods, including the kappa coefficient and generalized estimating equation (P<0.05). Results: Based on the findings of our study, the inter-observer agreement ranged from 58-100%, while the intra-observer agreement was reported to be around 100%. The difference in accuracy between 0.2 and 0.3 mm3 voxel sizes was not statistically significant (P>0.05). In addition, the accuracy of detecting different perforation sizes in the CBCT did not follow a specific pattern. Conclusion: This in vitro study showed that CBCT is a reliable diagnostic tool, and even in lower dosages of 0.3 mm3 voxel size, image resolution and diagnostic accuracy was not affected. Moreover, smaller root perforations could be detected as accurately as larger ones with CBCT.